2016
DOI: 10.1080/15384047.2016.1156273
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibits prostate cancer cell proliferation, migration, and tumor growth through upregulation of PEDF expression

Abstract: Metformin has been reported to inhibit the growth of various types of cancers, including prostate cancer. Yet the mode of anti-cancer action of metformin and the underlying mechanisms remain not fully elucidated. We hypothesized that the antitumorigenic effects of metformin are mediated through upregulation of pigment epithelium-derived factor (PEDF) expression in prostate cancer cells. In this report, metformin treatment significantly inhibited the proliferation and colony formation of prostate cancer cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 32 publications
5
63
0
Order By: Relevance
“…Recent studies have suggested that these hypoglycemic drugs, such as metformin, decrease the prostate specific antigen (PSA) level, epithelial-mesenchymal transition (EMT) and proliferation of PCa [48][49][50]. These studies confirm our present study showing that hyperglycemia drives PCa progressions.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies have suggested that these hypoglycemic drugs, such as metformin, decrease the prostate specific antigen (PSA) level, epithelial-mesenchymal transition (EMT) and proliferation of PCa [48][49][50]. These studies confirm our present study showing that hyperglycemia drives PCa progressions.…”
Section: Discussionsupporting
confidence: 92%
“…Men with diabetes have lower circulating testosterone concentrations, and decreased testosterone may reduce the risk of prostate cancer . Additionally, antidiabetic drugs, such as metformin, can directly influence the prostate cancer growth by inhibiting the proliferation, migration and invasion of the cancer cells . In co‐twin control analyses, the association of diabetes with prostate cancer became stronger suggesting that some familial factors or genes may partially contribute to the diabetes–cancer association, but cannot fully account for it.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 Additionally, antidiabetic drugs, such as metformin, can directly influence the prostate cancer growth by inhibiting the proliferation, migration and invasion of the cancer cells. 48 In co-twin control analyses, the association of diabetes with prostate cancer became stronger suggesting that some familial factors or genes may partially contribute to the diabetes-cancer association, but cannot fully account for it. Further studies are needed to identify which are the familial factors or genes that play a role in such an association.…”
Section: Discussionmentioning
confidence: 99%
“…Cell apoptosis was detected using the Annexin V-APC Apoptosis Detection kit (KeyGEN Biotech, Nanjing, China) as described in our previous studies and others [41,42,43,44]. Allophycocyanin (APC) is an accessory photosynthetic pigment found in blue-green algae.…”
Section: Methodsmentioning
confidence: 99%